Error Analysis in Academic Writing: A Case of EFL Students in North Central Timor - Febronia Lasi (UICELL, 2019)
The proposed study intended to investigate the different types of errors in academic writing performed by 20 English Foreign Language (EFL) Learners undertaking English for Academic Writing at English study program (ESP) University of Timor Indonesia. The learners were required to write a one page term paper assignment on a topic related to their hometown. The descriptive qualitative method was employed to examine and analyse the students’ term papers and interview. The analysis document became the primary source supported by the interview sections as references for the secondary sources. The errors in the term papers were identified and classified accordingly. The whole primary data were classified based on the types of errors, and they were explained. The result of the present study revealed that the errors majority carried out by the EFL learners due to the grammatical errors or sentences structure. Then, it followed by determiners, using capital letters, articles, and punctuation as the minor errors. The findings of this research were expected to provide the EFL learners positive input in learning English as a foreign language specifically in academic writing. Keywords: academic writing, error analysis, descriptive qualitative